Sufisme Sosial Syekh Yusuf Al-Makassari: Mengintegrasikan Spiritualitas dan Tanggung Jawab Sosial untuk Paradigma Etika Modern - Nurhayati (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study examines the social Sufism of Sheikh Yusuf al-Makassari (1626–1699) as an integrative framework bridging individual spirituality and collective social responsibility, offering a relevant paradigm for modern ethical challenges. Employing a qualitative library-research approach, it analyzes primary texts such as Zubdat al-Asrar and secondary sources (2020–2025) through systematic content analysis. The findings reveal three interconnected pillars. First, the integration of sharia, tariqa, and haqiqa rejects any dichotomy between external legal observance and inner spiritual depth, ensuring that spiritual refinement translates directly into ethical character and social action. Second, the concept of insan kamil is redefined not as an isolated mystical achievement but as an active, socially-engaged ideal embodying moderation, balance, justice, and tolerance. Third, Sheikh Yusuf's armed resistance against Dutch colonialism exemplifies how spiritual attainment inherently demands opposition to injustice, challenging the notion that mysticism precludes socio-political struggle. This paradigm demonstrates contemporary relevance across personal, communal, and structural dimensions: it fosters balanced character development, inspires socially responsible citizenship in pluralistic societies, and grounds activist movements in resilient spiritual values. Ultimately, this study offers a historically-grounded yet forward-looking model for integrating esoteric spirituality with public ethics, addressing modern crises of moral degradation, individualism, and social fragmentation